Blood management for elective orthopedic surgery - Palmer, AJR; Gagné, S; Fergusson, DA; Murphy, MF; Grammatopoulos, G (Lippincott, Williams & Wilkins, 2020)
—Strategies to conserve blood and reduce exposure to allogeneic blood improve outcomes after orthopaedic surgery. —A multidisciplinary team approach, including surgeons, anesthesiologists, hematologists, and other medical specialties, is required to deliver optimal blood management. —Key steps are to optimize preoperative hemoglobin levels, administer antifibrinolytics, use cell salvage for procedures with high blood loss, and adhere to restrictive transfusion thresholds.